The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/ejn.15122
|View full text |Cite
|
Sign up to set email alerts
|

Muscles in and around the ear as the source of “physiological noise” during auditory selective attention: A review and novel synthesis

Abstract: The sensitivity of the auditory system is regulated via two major efferent pathways: the medial olivocochlear system that connects to the outer hair cells, and by the middle ear muscles—the tensor tympani and stapedius. The role of the former system in suppressing otoacoustic emissions has been extensively studied, but that of the complementary network has not. In studies of selective attention, decreases in otoacoustic emissions from contralateral stimulation have been ascribed to the medial olivocochlear sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…In the case of MOCR measurements based on CAS, it is always possible for the signal to be contaminated by middle ear muscle responses (MEMRs), e.g., [ 36 ]. We did not use any special procedure to check for MEMRs within our TEOAE measurements, as our equipment did not provide such a facility.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of MOCR measurements based on CAS, it is always possible for the signal to be contaminated by middle ear muscle responses (MEMRs), e.g., [ 36 ]. We did not use any special procedure to check for MEMRs within our TEOAE measurements, as our equipment did not provide such a facility.…”
Section: Discussionmentioning
confidence: 99%
“…Francis et al (2018) reported that noise levels in the ear canal decrease when performing an auditory attention task [ 28 ]. Bell and Jedrzejczak (2021) also reported that the reduction of auditory peripheral response measured in the ear canal during a selective attention task may be attributed to the reflex contraction of muscles in and near the ear [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The human auditory system consists of afferent and efferent pathways that interact with each other while processing the auditory information. 1 The efferent pathways of the auditory system are believed to aid in selective attention, 2 3 protect the inner ear from auditory fatigability and acoustic trauma, 4 5 6 and improve the coding of signals embedded in noise, 7 8 9 speech perception in noise, 10 11 12 13 and sound localization in noise. 14 The role of efferent auditory pathways on speech perception in noise has received greater attention among researchers, 10 11 12 13 15 16 17 18 19 20 21 22 but their functional role in speech perception is not understood.…”
Section: Introductionmentioning
confidence: 99%